Data from: Evidence for past and present hybridization in three Antarctic icefish species provides new perspectives on an evolutionary radiation - Marino, Ilaria A. M.; Benazzo, Andrea; Agostini, Cecilia; Mezzavilla, Massimo; Hoban, Sean M.; Patarnello, Tomaso; Zane, Lorenzo; Bertorelle, Giorgio (Zenodo, 2013)
Determining the timing, extent, and underlying causes of inter-specific gene exchange during or following speciation is central to understanding species' evolution. Antarctic notothenioid fish, thanks to the acquisition of antifreeze glycoproteins during Oligocene transition to polar conditions, experienced a spectacular radiation to >100 species during Late Miocene cooling events. The impact of recent glacial cycles on this group is poorly known, but alternating warming and cooling periods may have affected species' distributions, promoted ecological divergence into recurrently opening niches, and/or possibly brought allopatric species into contact. Using microsatellite markers and statistical methods including Approximate Bayesian Computation, we investigated genetic differentiation, hybridization and the possible influence of the last glaciation/deglaciation events in three icefish species of the genus Chionodraco. Our results provide strong evidence of contemporary and past introgression by showing that: i) a substantial fraction of contemporary individuals in each species has mixed ancestry; ii) evolutionary scenarios excluding hybridization or including it only in ancient times have small or zero posterior probabilities; iii) the data support a scenario of interspecific gene flow associated with the two most recent interglacial periods. Glacial cycles might therefore have had a profound impact on the genetic composition of Antarctic fauna, as newly available shelf areas during the warmer intervals might have favoured secondary contacts and hybridization between diversified groups. If our findings are confirmed in other notothenioids, they offer new perspectives for understanding evolutionary dynamics of Antarctic fish, and suggest a need for new predictions on the effects of global warming in this group. Marino et al. genotypes Microsatellite genotypes used in the paper. Full description reported in the ReadMe file.